Culturing chelifers (Pseudoscorpions) that consume Varroa mites. (4th December 2013) - Read, S.; Howlett, B. G.; Donovan, B. J.; Nelson, W. R.; van, R. F.
Abstract Chelifers (Pseudoscorpions) are generalist predators of small prey such as mites. Their occasional presence in honeybee hives suggests potential to exploit them as part of a management programme against Varroa mites (Varroa destructor), a significant pest of honeybees. Two species of native New Zealand chelifers Nesochernes gracilis and Heterochernes novaezealandiae, shown to consume Varroa mites, were collected from commercial nucleus hives or in litter surrounding the hives. Methods for mass‐rearing the chelifers were developed to provide specimens for research and introduction into beehives for biological control of Varroa. Cultures were fed aphids and fruit fly larvae in vented containers containing sand and bark. N. gracilis was maintained at 14°C, 18°C, and 22°C. At 18°C, 1423 nymphs were reared from 140 N. gracilis adults, with 84.8% of all nymphs produced at this temperature. H. novaezealandiae was maintained at 18°C and 22°C, with 5 nymphs raised from 12 adults at 18°C and none at the higher temperature.